Occupant sensing in buildings : methods for occupant number, location and activity - Chen, Zhenghua (2017)
Since buildings account for some 40% of total energy usage in the world, great attentions have been paid on energy efficient buildings. To achieve this objective, occupant sensing is a key factor, which includes knowing the number of occupants, their locations and their performed activities in buildings. In this dissertation, we attempt to give solutions to the three corresponding questions of occupant sensing: How many occupants are there in a zone? Where are they located? What are they doing?